What distinguishes “intercultural professionals”? The experiences of male and femele graduates from the Intercultural University of the State of Puebla - Hernández Loeza, Sergio Enrique (2017)
A little more than ten years after the emergence of Intercultural Universities (UIs) in Mexico, their graduates begin to perform professionally in various spaces. Based on interviews with graduates of the Intercultural University of the State of Puebla, I analyze the tensions they face in a labor market characterized by precarization and insecurity, while seeking to identify the elements that distinguish them as «intercultural professionals». I conclude that the educational model of the UIs linked to the General Coordination of Intercultural and Bilingual Education promotes the formation of professionals capable of carrying out strategies to visualize cultural and linguistic diversity, but not necessarily with the intention of questioning or transforming the dominant political-economic system. Likewise, the labor spaces that are created or occupied by these new professionals are identified, as well as the «epistemic frictions» that they face when trying to enter the world of work, which are manifested in the way in which their decision-making is inserted in a conflict between dedicating their efforts to satisfy their personal needs and aspirations, or prioritizing work for the benefit of their community; all in a context of high rates of precarious work.